Riozim extranet procurement system. - Mandiya, Dadwell (Midlands State University, 2017)
This research gives a detailed overview of the Extranet Procurement System with the main thrust of identifying problems, summarizing facts, identifying and analyzing alternatives. Riozim has suffered data redundancies problems, human errors, fraud and biases in terms of choosing the best supplier, costs of employing much labor to manage every activity that was involved in the process, the system is rapacious thereby time consuming and may affects production and stimulates costs and also when providing periodic reports for administrative purposes among other problems.Commonly the orgnasation had endured late conveyance times and some of the time low quality products because of the current manual process of signing in a record by pen on paper particularly when they need to see the historical information of suppliers in accordance with the choice to choose one. Operating in this contemporary environment characterized by ever changing technology requires an orgnasation to adopt to new efficient technologies so as to remain competitive and ensures sustainability. This had contributed to the development of an automated system that is less prone to errors, do the systematic adjudication of suppliers price and delivery days ranking them accordingly, cost effective as well as evaluating supplier performance. PHP and MySQL was used to develop the system, utilizing the objectives as a guide to the development of the system together with the user requirements. During implementation of the system various testing strategies were done to check system functionality against user requirements. The organisation had fully implemented the system involving all the users from different departments and were being trained on how they interact with the system. The analyst developed maintenance schedule for the system so as to account for any changes that may arise. Recommendations were also documented for future development or system upgrade.